A new platform for the synthesis of diketopyrrolopyrrole derivatives via nucleophilic aromatic substitution reactions - Almodovar, Vitor A. S.; Tomé, Augusto C. (Beilstein Journal of Organic Chemistry, 2024)
Diketopyrrolopyrroles (DPPs) are a versatile group of dyes and pigments with valuable optoelectronic properties. In this work we report the synthesis of highly fluorescent DPP derivatives through straightforward nucleophilic aromatic substitution reactions with thiols and phenols. These nucleophilic substitutions occur at room temperature and manifest a remarkable selectivity for the 4-position of the pentafluorophenyl groups. Both symmetrical (disubstitution) and non-symmetrical (monosubstitution) DPP derivatives are formed in excellent overall yields. The optical properties of the newly synthesized compounds are also discussed. The new platform may be useful for bioorthogonal chemistry.
Keywords: diketopyrrolopyrrole; fluorescent dye; nucleophilic aromatic substitution; phenol; thiol